2021
DOI: 10.3390/diagnostics11112023
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease-Related Metabolic Pattern in Diverse Forms of Neurodegenerative Diseases

Abstract: Dementia is broadly characterized by cognitive and psychological dysfunction that significantly impairs daily functioning. Dementia has many causes including Alzheimer’s disease (AD), dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration (FTLD). Detection and differential diagnosis in the early stages of dementia remains challenging. Fueled by AD Neuroimaging Initiatives (ADNI) (Data used in preparation of this article were obtained from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…We observed that ADRP expression was elevated in DLB patients, probably on the account of overlapping pathology, topography of neurodegeneration and clinical presentation. Elevated ADRP expression in DLB patients in comparison to NC has been reported before ( Katako et al, 2018 , Lau et al, 2021 ). To account for overlapping topography we used an orthogonalization procedure to remove the contribution of AD-network and re-derived a pattern reflecting the “pure” DLB pathology, i. e. DLBRP ⊥ ADRP.…”
Section: Discussionsupporting
confidence: 64%
“…We observed that ADRP expression was elevated in DLB patients, probably on the account of overlapping pathology, topography of neurodegeneration and clinical presentation. Elevated ADRP expression in DLB patients in comparison to NC has been reported before ( Katako et al, 2018 , Lau et al, 2021 ). To account for overlapping topography we used an orthogonalization procedure to remove the contribution of AD-network and re-derived a pattern reflecting the “pure” DLB pathology, i. e. DLBRP ⊥ ADRP.…”
Section: Discussionsupporting
confidence: 64%
“…Unfortunately, the clinical notes for this patient did not include rationale for why no neuropsychological assessment was performed, or whether this patient required a neuropsychological assessment and/or exhibited cognitive deficits at a later point in time. Although a larger sample is needed to confirm these findings, our recent work also showed low levels of MAD+ designations in healthy controls, those with stable MCI (not progressing to AD for >3 years) [ 30 , 34 ], and primary psychiatric disorders [ 34 ].…”
Section: Discussionmentioning
confidence: 92%
“…PET data were preprocessed and analyzed in SPM12 software (version 7487, RRID:SCR_007037; Wellcome Trust Centre for Neuroimaging, London, UK, (accessed on 19 February 2020)) using MATLAB (version r2018a, The MathWorks Inc., Natick, MA, USA), as described elsewhere [ 30 , 34 ]. Briefly, FDG-PET images were spatially normalized to standard MNI space for PET (using “Old Normalize” as this does not require T 1 -weighted images), then smoothened with an 8 mm full-width half-maximum Gaussian smoothing kernel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other tracers that bind to specific proteins that characterizes AD such as florobetapir [ 25 ], florbetaben [ 26 ], flutemetamol [ 27 ], and flortaucipir [ 28 ], the FDG uptake level represents overall “health” of the brain regions, the decline of which is potentially associated with neuronal loss, mitochondrial dysfunction, loss of synaptic activities, or a combination of these [ 29 ]. In fact, we have recently demonstrated that MAD scores were also elevated in some patients with other types of dementia such as dementia with Lewy bodies, frontotemporal dementia, and primary progressive aphasia, suggesting the non-specificity of FDG-PET-based markers for AD in non-AD dementia [ 30 ]. And, it has been previously demonstrated that AD patients also show an accelerated pattern of morphological [ 31 ] and metabolic [ 32 ] changes associated with healthy aging itself.…”
Section: Discussionmentioning
confidence: 99%